Physico-chemical and sensory characterization of sweet biscuits made with Yacon flour (Smallanthus sonchifolius) - Mónica Simanca-Sotelo; Claudia De Paula; Yina Domínguez-Anaya; Yenis Pastrana-Puche; Beatriz Álvarez-Badel (NFS Journal, 2021)
Yacon (Smallanthus sonchifolius) is a sweet-tasting tuber, grown in the Andes Mountains and considered a functional food because of its fructooligosaccharide (FOS) content. The objective of the research was to characterize physicochemically and sensorially sweet biscuits made with a mixture of wheat flour and yacon flour. The selected yacon fruits were washed with sodium hypochlorite (200 ppm), peeled, sliced and dried at 55 °C/72 h in a forced convection tray dryer (Binder UDK 250) to obtain flour; then their approximate centesimal composition and color were determined, and subsequently sweet biscuits were made using three wheat/yacon flour mixtures in the following proportions (w/w): 100:00 (control), 70:30, 60:40 and 50:50; a completely randomized design with three repetitions was used. The biscuits were physicochemically characterized using AOAC (Association of Official Analytical Chemists) techniques; their caloric intake was calculated and an acceptance test was performed with 50 consumer tasters using a 9-point hedonic scale. The yacon flour presented a moisture and protein content lower than some references, and ethereal extract, fiber and ash were similar to those reported in the literature; in terms of color the flour presented a lower value than wheat flour, indicating that it is darker. Cookies with mixed wheat flour/yacon flour had a high content of ethereal extract, fiber, ash and carbohydrates, and statistical differences (p ≤ 0.05) when compared with the control; the caloric value of cookies was between 375.32 and 386.04 Kcal/g. The sensory acceptance test showed significant differences for all the attributes evaluated, highlighting the treatment with 70:30 wheat/yacon flour with the highest scores for the attributes of appearance, aroma, texture and flavor. Based on the results, it is concluded that obtaining flour and making cookies with mixtures of wheat flour/yacon flour can be an alternative use of the fruit.